Cash on trial, mk II: Economics, technology and institutions - Urs W. Birchler; Ernest Gnan; Carl-Christoph Hedrich; Jens Ulbrich (SUERF - The European Money and Finance Forum, 2019)
The conference will be staged as a court trial in which cash will be accused with three charges: First, cash is an essential part of many kinds of criminal activities; second, it is an inefficient and outdated means of payment; and third, it prevents central banks from implementing optimal monetary policy in times when price stability would require negative interest rates. To spur a lively discussion we intend to develop the conference in a defense and prosecution part, where witness' are called to elaborate on the charges. Additional presentations will provide a neutral overview of the current situation of the use of cash in the Eurosystem and of ideas to develop a digital cash by central banks.
Keywords: C80; C82; E02; E42; E50; H56; K42; O17; Y1; 330; cash; central bank digital currencies; cash limit; crime; corruption; financial proceeds; money laundering; money; monetary theory; zero lower bound